PENGARUH K3 DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT PERTAMINA (PERSERO) MARKETING OPERATION REGION IV - Ade Maulana Aminudin; Apriatni Endang Prihatini; Reni Shinta Dewi (Universitas Diponegoro, 2015)
HSE implementation and compensation are the factors that may increase employees performance. Based on preface survey in PT PERTAMINA (Persero) MOR IV there are some problems about HSE and compensation that unsuitable with occupation responsibility.The purpose of study was to know HSE and compensation had influence to employees performance partially and simultaneously. The analysis used qualitatif analysis and quantity analysis that were including data quality test, crosstab, corelation test, regression test, and significant test by SPSS 20.0 software. The test results demonstrate that HSE and compensation had influence to employees performance partially and simultaneously. Based on double regression test with signification 0.020, that means HSE had influence more significant than compensation to employees performance at PT PERTAMINA (Persero) MOR IV. PT PERTAMINA (Persero) MOR IV should to equip the HSE tools completesly by adding masker and adjust the employees allowance with job result for increasing employees performance too.